Desenvolvimento da autonomia na aprendizagem de língua inglesa em sala de aula: a visão da professora-pesquisadora - Andrade, Flávia Luciana Campos Dutra (2016)
The purpose of this study, which belongs to the area of Applied Linguistics and to a project entitled Language in the Development of an Educator, is to reflect on this professor-researcher’s teacher training, aiming to contribute to the development of autonomy in English language learning on the part of students of a High School Technical Program in Animal Husbandry. The specific purposes are: (a) to narrate classes in a reflective journal; (b) to identify actions performed which aimed to contribute to the development of students’ learning autonomy; (c) to conduct a linguistics-based data analysis on the contribution of her actions to promote autonomy; (d) to discuss teacher training focusing on the development of students’ autonomy. Accordingly, our data were generated by the professor-researcher, who described in her reflective journals (REICHMANN, 2013) how classes were conducted during a school semester and critically reflected on them. This is a qualitative case study with a documentary procedure. Theoretical framework which supports our data analysis involves concepts on English language teaching (PAIVA, 2012; OLIVEIRA, 2014); autonomy (PAIVA, 2012; OLIVEIRA, 2014); teacher training focusing on critical reflections (NÓVOA, 2015; CELANI; PINHEIRO, 2010; ALMEIDA FILHO, 2009); and language and teacher identity (MOITALOPES, 1998; ROMERO, 2008). Additionally, our analysis is linguistically based on Halliday’s systemic functional grammar, focusing on transitivity (HALLIDAY, 1994; FUZER; CABRAL, 2014). Our results suggest that the professor-researcher’s actions contributed to promote students’ autonomy, considering the way that classes were conducted, i.e., students were encouraged to think and find answers, instead of being given answers promptly without any effort. In addition, the professor-researcher was able to perceive the importance of the critical reflection process to comprehend and resignify her own teacher identity.